Big Data Security using Homomorphic Encryption - R.Kanagavalli, Bhagyashri R Hanji, Sushmitha S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the swift growth of communication technology, the data size and the rate at which data being generated has considerably increased known as big data era. One of the vital challenges that are faced by the application environments is getting big data secured. Homomorphic Encryption (HE) schemes, a special direction of cryptography can be adopted to address big data security issues. In this paper, we have presented big data security model along with HE schemes.